A system for the hydrodynamic design of tension leg platforms of floating wind turbines. (1st January 2019) - Uzunoglu, E.; Guedes Soares, C.
Abstract: A system that allows testing new concepts quickly and with higher precision is developed and demonstrated through an example of a tension leg platform. The process goes through the mass matrix estimations, hydrostatics, mooring system design, and dynamic analysis. It starts from a multi-purpose 3D model and does not require user intervention or moving data between software. Instead, the same quadrilateral mesh is used for all calculations after modifying a format used by panel method codes. The need to use simplified tables and spreadsheets is eliminated. The frequency domain wave responses are obtained with a potential flow solver and assessed to approximate the platform's performance with the wind turbine. The assessment includes the detection of slack mooring occurrences. The setup allows completing the initial design with minimal amount of input data. A time domain model for simulations is also built within the system. The level of agreement between these two solutions is examined. The platform is assumed to operate in Galicia, Spain, to discuss sets of environmental conditions considering the mooring line responses. Two primary variables are used to illustrate a sizing algorithm on 231 hull variations. A measure of performance is given to clarify the required time for the design space assessment with this method.